Immersion effect of autopolymerization silicon soft denture liner in sodium hypochlorite solution on water absorption and color stability - Auliana, Amirah Najla; Dahar, Eddy; Wahyuni, Siti (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2024)
ABSTRACTIntroduction: The long-term use of soft denture liner (SDL) can create an anaerobic environment in the oral cavity, which supports the growth of Candida albicans and increases the risk of denture stomatitis. Sodium hypochlorite (0.5%) is effective in inhibiting this growth. This study aims to investigate the effects of immersion and the differing durations of immersion of silicone-based SDL in sodium hypochlorite on water absorption and color stability over 2.5 and 5 days. Methods: This study is a laboratory experimental design involving 24 SDL samples (15×2 mm) divided into four groups. Groups A and C were immersed in 0.5% sodium hypochlorite, while groups B and D were immersed in distilled water for 2.5 and 5 days. Water absorption was measured using an analytical balance, and color stability was assessed with a CS-10 colorimeter. Data analysis used an independent T-test. Results: The independent T-test indicated significant effects of immersing SDL in 0.5% sodium hypochlorite for both 2.5 days and 5 days on water absorption, with p-values of 0.005 and 0.0001. There was also a significant effect on color stability for both durations, with a significance value of p=0.0001. There were significant differences in the effects of immersion duration between the 2.5-day and 5-day groups regarding both water absorption and color stability, with significance values of p=0.0001. Conclusion: The use of sodium hypochlorite as a SDL cleaner can affect water absorption and color stability; a 0.5% concentration can be used as a cleaning agent because it remains within a clinically acceptable range.KEY WORDS: Soft denture liner, 0.5% sodium hypochlorite, water absorption, color stabilityPengaruh perendaman soft denture liner autopolimerisasi berbahan silikon dalam larutan natrium hipoklorit terhadap penyerapan air dan stabilitas warna : studi eksperimentalABSTRAKPendahuluan: Penggunaan soft denture liner (SDL) jangka panjang dapat menciptakan lingkungan anaerobik di rongga mulut, yang mendukung pertumbuhan Candida albicans dan meningkatkan risiko denture stomatitis. Natrium hipoklorit 0,5% efektif menghambat pertumbuhan ini. Penelitian ini bertujuan untuk mengetahui pengaruh perendaman dan perbedaan pengaruh lama perendaman SDL berbahan dasar silikon dalam natrium hipoklorit terhadap penyerapan air dan stabilitas warna selama 2,5 dan 5 hari. Metode: Rancangan penelitian adalah eksperimental laboratoris dengan 24 sampel SDL (15×2 mm) dibagi menjadi 4 kelompok. Kelompok A dan C direndam dalam natrium hipoklorit 0,5%, sedangkan B dan D dalam akuades selama 2,5 dan 5 hari. Penyerapan air diukur dengan timbangan analitik, dan stabilitas warna diuji dengan colorimeter CS-10. Analisis data menggunakan uji T independen. Hasil: Berdasarkan uji T Independen terdapat pengaruh signifikan pada perendaman SDL dalam natrium hipoklorit 0,5% selama 2,5 dan 5 hari terhadap penyerapan air dengan nilai p=0,005 dan p=0,0001. Terdapat pengaruh signifikan pada perendaman SDL dalam natrium hipoklorit 0,5% selama 2,5 dan 5 hari terhadap stabilitas warna dengan nilai signifikansi keduanya p=0,0001. Terdapat perbedaan pengaruh lama perendaman antara kelompok perendaman SDL dalam natrium hipoklorit 0,5% selama 2,5 hari dengan 5 hari terhadap penyerapan air dengan nilai signifikansi p=0,0001 dan terdapat perbedaan pengaruh lama perendaman antara kelompok perendaman SDL selama 2,5 hari dengan 5 hari terhadap stabilitas warna dengan nilai signifikansi p=0,0001. Simpulan: Penggunaan natrium hipoklorit sebagai bahan pembersih SDL dapat memengaruhi penyerapan air dan stabilitas warna, konsentrasi 0,5% dapat digunakan sebagai bahan pembersih karena masih berada dalam rentang nilai yang dapat diterima secara klinisKATA KUNCI: Soft denture liner, natrium hipoklorit 0,5% , penyerapan air, stabilitas warna